7=(t-1)-2(t-3)

Simple and best practice solution for 7=(t-1)-2(t-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7=(t-1)-2(t-3) equation:


Simplifying
7 = (t + -1) + -2(t + -3)

Reorder the terms:
7 = (-1 + t) + -2(t + -3)

Remove parenthesis around (-1 + t)
7 = -1 + t + -2(t + -3)

Reorder the terms:
7 = -1 + t + -2(-3 + t)
7 = -1 + t + (-3 * -2 + t * -2)
7 = -1 + t + (6 + -2t)

Reorder the terms:
7 = -1 + 6 + t + -2t

Combine like terms: -1 + 6 = 5
7 = 5 + t + -2t

Combine like terms: t + -2t = -1t
7 = 5 + -1t

Solving
7 = 5 + -1t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add 't' to each side of the equation.
7 + t = 5 + -1t + t

Combine like terms: -1t + t = 0
7 + t = 5 + 0
7 + t = 5

Add '-7' to each side of the equation.
7 + -7 + t = 5 + -7

Combine like terms: 7 + -7 = 0
0 + t = 5 + -7
t = 5 + -7

Combine like terms: 5 + -7 = -2
t = -2

Simplifying
t = -2

See similar equations:

| 9+3x=-(x+7) | | 16-x=4+5x | | h=-4t^2+4t+120 | | x^3+3x^2+2x=2x^2+4x | | 3(x-8)+15=-18 | | -1=-14+5x | | 10x-8=10x+5 | | b=zc+m | | 77r^2+53r-40=0 | | 4(x+5)=3(x-2)-2x+2 | | 42*84*3.14=x | | 3x^3-x^2-10x=-x^2+2 | | Y+9.4=10 | | 10x*4=80 | | 3x-15=120 | | 11-11x=-14-10x | | -a+8.5=14.2 | | -3(5+5m)=75 | | 1x+8=5 | | -6(10+2x)=-192 | | 3s^2+7s^2-18s-42=0 | | 3x-6=x-3 | | k-9=11 | | 0.6(-6.53-2x)=-0.4x | | 8x-9=3-2x | | (x-9)(3x-1)=-52x-39 | | 2(x-1)-6= | | 7sin^2(x)-3=0 | | 1-(3x+4)2=(4x-1)2-(5x+2)2 | | x-7=7x+5 | | -2.0p=5(10-0.5p) | | 6-4x-7x^3=0 |

Equations solver categories